Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian Pada E-Commerce Shopee: Studi Pada Mahasiswa Prodi Administrasi Bisnis Universitas Nusa Cendana - Lema, Dominique Julied Saputri; Mesakh, Anthonius B.; Kasim, Abas (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research aims to know and analyze both the partial and simultaneous effects of online customer review and online customer rating on the purchase decision on e-commerce Shopee among students of the business administration program of Nusa Cendana University. The number of samples in this research was 100 respondents, with using the Purposive Sampling technique. The data analysis techniques used are quantitative descriptive analysis, multiple linear regression analysis, and hypothesis testing and analysis of the coefficient of determination (R2) using the SPSS V26 application. From the results of Multiple Linear Regression Analysis, the equation is obtained: Y = 2.301 + 0.302X1 + 0.705X2 + 2.699. The results of both the t test and the F test show that partially online customer review and online customer rating have a positive and significant effect on purchasing decision. Based on the Adjusted R² value, the contribution of the perceived usefulness and trust variables to intention to use is 61,1%, while the remaining 38.9% of purchase decision variables were influenced by other variables not discussed in this study. For this reason, it is suggested that further researchers can examine variables outside of this study that can affect purchasing decisions, as well as not only Shopee e-commerce but also other types of e-commerce.